Annual Report to the Nation on the Status of Cancer, featuring state‐level statistics after the onset of the COVID‐19 pandemic - Sherman, Recinda L.; Firth, Albert U.; Henley, S. Jane; Siegel, Rebecca L.; Negoita, Serban; Sung, Hyuna; Kohler, Betsy A.; Anderson, Robert N.; Cucinelli, James; Scott, Susan; Benard, Vicki B.; Richardson, Lisa C.; et al. (Cancer, 2025)
ABSTRACT Background This report represents a collaborative effort by the major cancer surveillance organizations to present the definitive US statistics for cancer incidence and mortality. Methods Cancer incidence data were obtained from population‐based cancer registries funded by the Centers for Disease Control and Prevention and the National Cancer Institute and compiled by the North American Association of Central Cancer Registries. Cancer death data were obtained from the National Center for Health Statistics' National Vital Statistics System. Statistics are reported by cancer type, sex, race and ethnicity, and age. The potential impact of the coronavirus disease 2019 (COVID‐19) pandemic on incidence was assessed by using state‐level changes compared with previous years, the stringency of COVID‐19 policy restrictions, the magnitude of COVID‐19 death rates, and changes in the use of mammography. Results Overall cancer incidence rates per 100,000 were 500 among males and 437 among females. Excluding 2020, cancer incidence rates remained stable (2013–2021) among males and increased 0.3% per year on average (2003–2021) among females. The overall cancer death rate per 100,000 was 173 among males and 126 among females. Cancer death rates decreased by 1.5% per year (2018–2022), slowing from a previous 2.1% decline. Cancer incidence in 2020 declined from prepandemic levels for all demographic groups examined. However, the magnitude of decline was not strongly associated with the study's proxies for health care capacity, health care access, or COVID‐19 policies. Conclusions Overall cancer mortality declined over 20 years, even during the COVID‐19 pandemic. Disruptions in health care use early in the pandemic resulted in incidence declines in 2020, but 2021 incidence returned to prepandemic levels. The American Cancer Society, the Centers for Disease Control and Prevention, the National Cancer Institute, and the North American Association of Central Cancer Registries collaborate to provide annual updates on cancer occurrence and trends in the United States and to address a special topic of interest. This year, the special topic compares how cancer statistics have changed across geography because of the coronavirus disease 2019 pandemic.